Electric Field Distribution Analysis of Blood Cancer as a Potential Blood Cancer Therapy - Firdhaus, Miftakhul; Farahdina, Ulya; Zulfa, Vinda Zakiyatuz; Endarko, Endarko; Rubiyanto, Agus; Nasori, Nasori (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2021)
Blood cancer causes a significant increase in the concentration of Leukocytes, which can be broken down through dielectrophoresis and electrochemical procedures. Therefore, the electric field plays an important role in the migration of leukocytes to high voltage areas. This is because different electrode arrangements produce varying electric field distributions. Furthermore, this study applied finite element methods to generate electric fields when electrodes with an AC voltage were applied to blood placed in a chamber. Therefore, in this study, variations of mediums and electrode arrangements were investigated, which led to the recommendation of 3 models. The objective was to investigate electrode arrangements that produce optimal electric field distribution for the three models to exhibit a booster of electric field distribution. The maximum electric field is generated close to the electrode (Z=2 mm and Z=92 mm) for any material (i.e. normal blood, B lymphocyte, and T lymphocyte) with values of 22.6 V/m and 23.47 V/m, 22.85 V/m and 22.97 V/m, and 24.88 V/m and 25.01 V/m. Based on principle, lymphocytes in the blood result in positive dielectrophoresis, since they migrate to a higher electric field close to the electrode, with enough input voltage to turn the electrochemical process on the leukocytes into electric current. Furthermore, this study provides new perspectives and ideas, which have not been revealed in previous studies on blood cancer therapy using the electric field of Ag electrode in blood cancer distribution.Keywords: blood cancer, dielectrophoresis, electric field, voltage, electrochemical, and cancer therapy.